Annual Plan 2004-2005 Government of Jharkhand - Planning Commission (Planning Commission, 2004)
Jharkhand, India's youngest and 28th State came into existence 15th November 2000 by separating 18 districts of Chotanagpur and Santhal Paragana region from Bihar. The State is rich in mineral and forest resources. The average rainfall is about 1200 mm spread over four monsoon months Agriculture is the mainstay of the population. State represents primarily monocropping system with rice as main crop. The State has at present 22 Strikes constituting of 211 development blocks (including tribal development blocks and 3759 village panchayats. There are I municipal corporation, 2.0 municipalities and 22 notified area committees as urban local bodies. Besides Ranchi Regional Development Authority (RRDA), Mining Areawise Development. Authority (MADA - Dhanbad) and Hazaribagh Mines Board are authorities functional with their separate identity & charter.
Planning & Development Department Government of Jharkhand